Enhancing Informatics Engineering students' speaking skills at Asahan university using picture media in present tense - Derliana Hasibuan; Datulina Ginting; Dian Anggraini Harahap (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2024)
The ability to speak English with good and right pronunciation, accuracy, fluency, and intonation is a test for university students of the Informatics Engineering Department at the University of Asahan to achieve new knowledge. There are still many university students who are not good at speaking skills in English. Therefore, this study aims to evaluate the implementation of image media techniques to students' speaking skills in the present tense. This research is descriptive qualitative research. This research was conducted in three cycles, each consisting of two learning cycles or face-to-face. The research subjects were 20 education participants. The methods used to collect data are observation, interviews, and tests. The instrument used to obtain data is a test question. The data analysis technique used is descriptive qualitative and quantitative analysis. The results showed that university students in cycles I, II, and III had an average score which indicated that image media techniques could enhance English speaking skills in the present tense. It was summarized that the implementation of image media could effectively enhance the ability to speak English. Picture media can help university students understand English. This finding can also be used as a reference for lecturers to enhance the speaking-learning process Keywords: picture; media; speaking; EFL.